Virus infections in bone marrow transplant recipients: a three year prospective study. Issue 8 (August 1990) - Taylor, C E; Sviland, L; Pearson, A D; Dobb, M; Reid, M M; Kernahan, J; Craft, A W; Hamilton, P J; Proctor, S
Abstract : Over three years 81 consecutive bone marrow transplant recipients (32 allogeneic and 49 autologous) who received prophylaxis with acyclovir, were studied for symptomatic virus infection. Thirty nine infections were documented in a total of 28 patients. Thirty two infections were mild, five were moderately severe, and two were severe. Cytomegalovirus infection occurred in only six allogeneic recipients. Herpes simplex virus and varicella zoster virus infections occurred infrequently. Seven patients who were considered at the time of death to have died due to an infectious cause were studied virologically at necropsy. In only one patient was a virus infection thought to have been the cause of death. Prophylaxis with acyclovir may have influenced the rate and clinical prominence of herpes virus infections. In this study viruses were considered to have had a relatively minor role in causing morbidity and mortality.